(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Anthropomorphism, the attribution of human characteristics to non-human entities, is a ubiquitous feature in mass media. This article explores the cultural implications and social influence of anthropomorphism in media, with a focus on the comparison between Western and Eastern media. By examining how anthropomorphic representations impact societal values, social behavior, and cultural norms, this study offers insights into the different ways anthropomorphism shapes public consciousness. The article demonstrates that, while both Western and Eastern media use anthropomorphism to convey key cultural messages, the emphasis on individualism versus collectivism, as well as environmental consciousness, varies significantly across these cultural contexts.